Correlation between brain injury biomarkers and Glasgow coma scale in pediatric sepsis - Nahari Arifin; Irawan Mangunatmadja; Antonius Pudjiadi; Sudung O. Pardede (Indonesian Pediatric Society, 2012)
Background Sepsis in children, with or without multiple organfailure, causes increased susceptibility to brain injury due tosystemic insults. Brain injury in sepsis is difficult to recognizeclinically. Neuron-specific enolase (NSE) and S-lOOB have beenextensively studied in brain injuries and appear to be promisingalternative biomarkers.Objectives To determine if there is a correlation between theGlasgow coma scale (GCS) and NSE as well as S-lOOB levels, inchildren with sepsis.Methods We performed an analytical study on septic childrenaged > 2 years. GCS scores were assessed on the first and thirddays of admission. Blood specimens to test for NSE and S-lOOBwere drawn on the first day of admission and stored at -70QC forfurther analysis at the end of the study.Results Out of 35 patients, 30 met the inclusion criteria. Postanalysis,one subject with NSE above the maximum level wasexcluded. Negative correlations were found between GCS scoreand NSE, as well as between GCS and S-lOOB levels. Analysisrevealed a significant ROC for NSE, but not for S-lOOB. NSEconcentration of 8.1 /.lg/L was the cut-off point for GCS scoresbelow 12.Conclusions There were negative correlations between GCSand NSE levels, as well as between GCS and S- lOOB levels. Thepredictive value ofNSE level was a cut-off point of 8.1 /.lg/L forGCS scores below 12. [Paediatr lndones. 2012;52:111-17]